2015
DOI: 10.1097/igc.0000000000000395
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Urogynecological Morbidity, and Lymphedema After Radical Vaginal Trachelectomy for Early-Stage Cervical Cancer

Abstract: Patients treated with RVT for early-stage cervical cancer had persistent bladder emptying problems and lymphedema comparable to those experienced by patients treated with RAH and significantly higher than those reported by healthy control women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…The mean value of lymphedema in this study was among the highest five values aside from sexual worry, menopause symptoms, body image, and symptoms experienced. Other studies noted similar findings where a significant number of the participants reported lymphedema related symptoms (Frøding, Ottosen, Mosgaard, & Jensen, 2015;Lee et al, 2016). In patients with cervical cancer, treatment modalities, including chemotherapy and radiotherapy in the pelvic area, exacerbates the symptoms of lymphedema.…”
Section: Discussionsupporting
confidence: 60%
“…The mean value of lymphedema in this study was among the highest five values aside from sexual worry, menopause symptoms, body image, and symptoms experienced. Other studies noted similar findings where a significant number of the participants reported lymphedema related symptoms (Frøding, Ottosen, Mosgaard, & Jensen, 2015;Lee et al, 2016). In patients with cervical cancer, treatment modalities, including chemotherapy and radiotherapy in the pelvic area, exacerbates the symptoms of lymphedema.…”
Section: Discussionsupporting
confidence: 60%
“…Two studies evaluated the incidence of LLL in patients who underwent radical trachelectomy, reporting an incidence of 11% (44) and 24.1% (45) respectively (both relying on subjective evaluations). In the study of Frodig et al, women who underwent trachelectomy had persistent LLL comparable to that experienced by patients treated with radical abdominal hysterectomy and significantly higher than those reported by healthy control women (p=0.031) (44). This is not surprising as lymphadenectomy is performed in trachelectomy as well.…”
Section: Incidencementioning
confidence: 67%
“…Conversely, other studies reported no differences between the laparoscopic and the laparotomic lymphadenectomy procedure (1,44). Comparing abdominal radical hysterectomy versus robotic radical hysterectomy, LLL was significantly higher in the laparotomic group (27.5% vs. 8.3%, p=0.001) (50).…”
Section: Incidencementioning
confidence: 74%
“…Prior to the introduction of sentinel lymph node mapping, the rates of treatment-related lower extremity lymphedema ranged from 10%24 when assessed retrospectively to 41%25 when prospectively assessed using objective metrics. The rates of lower extremity lymphedema after fertility-sparing surgery with radical trachelectomy fall within this range at 24%, as lymphadenectomy is also done in these cases 26…”
Section: Secondary Lymphedema In Gynecologic Malignanciesmentioning
confidence: 98%